PERAN PEMBINA ASRAMA DALAM MENUMBUHKAN KEDISIPLINAN SANTRI DI LPK JAMILURRAHMAN PUTRI YOGYAKARTA - Nurwahidah, Yelis; Pebrianti, Nadia; Faidah, Kharisma Nur; Amini, Suti (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to analyze the role of dormitory coaches in fostering santri discipline at LPK Jamilurrahman Putri, focusing on discipline coaching strategies through exemplary, habituation, rules, and interpersonal interactions, as well as the challenges faced by coaches in creating a conducive dormitory environment. This research uses a descriptive qualitative approach with data collection through in-depth interviews with dormitory guardians, musyrifah, and santri. Data were thematically analyzed through transcription, coding, and pattern drawing stages to identify strategies, supporting factors, and obstacles to discipline formation, and validated through data triangulation from various sources. The results showed that dormitory coaches play a central role in fostering santri discipline through the preparation of schedules, application of rules, habituation, exemplary, and personal approaches, where emotional closeness between coaches and santri facilitates the internalization of disciplinary values. This research emphasizes that santri discipline is not simply the result of formal rules, but is an internalization of values formed through human interaction and daily exemplary, thus making a new contribution to the study of dormitory-based character education in the context of modern Islamic education.